2014
DOI: 10.1002/chin.201417016
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Cyclic Tungstoselenites Based on {Se2W12} Units.

Abstract: Cyclic Tungstoselenites Based on {Se2W12} Units. -Compounds (III) and (V) are characterized by single crystal XRD, 77 Se NMR, FTIR, and Raman spectroscopy. (III) contains the novel macrocyclic anion [{(Se2W12O46)WO(H2O)}3] 24consisting of three Se2W12 fragments, which are connected via three WO(H2O) 4+ groups. The same Se2W12 building block is present in the structure of (V). The hydration numbers of (III) and (V) determined by XRD differ from those determined by thermal and elemental analysis. Na 24 [H 6 Se 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Every Ru atom inside favored a distorted octahedron consisting exclusively of bridging oxo ligands, and the Ru−O distances ranging from 1.763 to 2.050 (10) Å are comparable to the corresponding distances in the Ru IV -containing polyanions. [26][27][28][29][30]51 The BVS calculations also gave BVS values of 4.114−4.250 for Ru(IV) and 5.957−6.201 for all W(VI) atoms (Table S5). Within the {W 8 } building block (Figure 1f), four WO 6 octahedra were connected via edges leading to a {W 4 } semicircle; then, these two {W 4 } fragments were further connected via two corners to form the {W 8 } ring.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
“…Every Ru atom inside favored a distorted octahedron consisting exclusively of bridging oxo ligands, and the Ru−O distances ranging from 1.763 to 2.050 (10) Å are comparable to the corresponding distances in the Ru IV -containing polyanions. [26][27][28][29][30]51 The BVS calculations also gave BVS values of 4.114−4.250 for Ru(IV) and 5.957−6.201 for all W(VI) atoms (Table S5). Within the {W 8 } building block (Figure 1f), four WO 6 octahedra were connected via edges leading to a {W 4 } semicircle; then, these two {W 4 } fragments were further connected via two corners to form the {W 8 } ring.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
“…Similarly, Krebs and co-workers have reported the [Sb 2 W 22 O 74 (OH) 2 ] 12− comprising two {β-SbW 9 O 33 } 9− units linked by a belt of two {WO 2 } 2+ and two {WO 2 (OH)} + groups. 15 Then, a series of such sandwich tungsten clusters, like [Bi 2 W 2 2 O 7 4 (OH) 2 ] 1 2 − , 1 6 [ T e 2 W 2 0 O 7 0 ( R u C 6 H 6 ) 2 ] 8 − , 1 7 a n d 18 were also reported (Figure S1). Step two, polyanion 1 assembled into the Na 5.5 H 6.5 •1•36H 2 O rod-like ionic crystal with layered structure through the Na-bridged sheet and hydrogen-bonded layers.…”
Section: Resultsmentioning
confidence: 97%
“…With that, it was concluded the proton transport process of compound 1 is supported by a Grotthus mechanism for its E a residing in the range of 0.1−0.4 eV. 31 Several proton conductivity studies have been reported recently in the field of POMs, such as {[W 14 Ce IV 6 O 61 ]-…”
mentioning
confidence: 99%
“…In addition, most of the related studies focused on POMs built from 3d block transition metals and lanthanide elements, while rare studies were conducted on 4d block transition metal-based POMs in this field. 31 and Niu group reported an organic hybrid antim o n i o t u n g s t a t e l a y e r e d i o n i c c r y s t a l Na 5.5 H 6.5 [(SbW 9 O 33 ) 2 {WO 2 (OH)} 2 {WO 2 }RuC 7 H 3 NO 4 ]• 36H 2 O with high proton conductivity in 2023. 32 Here we reported a new hexamer Na The proton conductivity of compound 1 was explored and showed a decent performance of reaching 5.41 × 10 −3 S cm −1 at 333 K and 55% relative humidity (RH), as per the Grotthus mechanism.…”
mentioning
confidence: 99%